Application of the CIRC (Cooperative Integrated Reading and Compotision) Learning Model to Improve Student Learning Outcomes on the Main Material of a Paragraph - Erni Kurniawati (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve students' ability to find the subject matter of a paragraph. This research is a classroom action research (PTK) which is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fifth grade students of SD Negeri Buniwah 01, Sirampog District, Brebes Regency in the academic year 2020/2021, totaling 17 students. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of the CIRC (Cooperative Integrated Reading And Composition) learning model can improve learning outcomes in finding the main thoughts of a paragraph in grade V SD Negeri Buniwah 01 in the 2020/2021 academic year as evidenced by the percentage of completeness of learning outcomes in cycle I of 64, 7% to 88.2% in cycle II.